2010
DOI: 10.1007/s00148-010-0342-8
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and economic fluctuations

Abstract: Using wavelet methods, this paper analyzes the relationship between the age-adjusted, infant, and cause-specific mortality rates and the business cycle in Sweden over the period 1800-2000 (1911-1996 for cause-specific mortality). For the period 1800-2000, an increase in GDP by 1% decreased mortality by 0.7%. This overall relationship is due to a strong counter-cyclical relationship in the nineteenth century, which disappeared in the twentieth century. In contrast, in the twentieth century higher mortality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Second, the hidden cointegration methodology introduced by Hatemi (26) was used to model the asymmetric effects of business cycles on population health in both long-and short-run. The asymmetric effects identified by our empirical model fill the gap of previous studies using the individual time series of advanced economies (9,21,22,28,29,49) and reconcile results from prior studies that document a pro-cyclical pattern between business cycles and population health (27)(28)(29)57) with other studies suggesting the changing relationship between business cycles and population health (12,21,22,36,49). This study, nevertheless, suffers from several limitations: First, our cointegrating analyses restricted in the bivariate type of analyses because the time series data regarding socio-economic variables other than real GDP per capita and life expectancy at birth across the ASEAN countries is too short to perform a reliable time series analyses.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Second, the hidden cointegration methodology introduced by Hatemi (26) was used to model the asymmetric effects of business cycles on population health in both long-and short-run. The asymmetric effects identified by our empirical model fill the gap of previous studies using the individual time series of advanced economies (9,21,22,28,29,49) and reconcile results from prior studies that document a pro-cyclical pattern between business cycles and population health (27)(28)(29)57) with other studies suggesting the changing relationship between business cycles and population health (12,21,22,36,49). This study, nevertheless, suffers from several limitations: First, our cointegrating analyses restricted in the bivariate type of analyses because the time series data regarding socio-economic variables other than real GDP per capita and life expectancy at birth across the ASEAN countries is too short to perform a reliable time series analyses.…”
Section: Discussionmentioning
confidence: 55%
“…Previous empirical findings have found that the relationship between business cycles and population health could be positive (27)(28)(29)57), negative (5)(6)(7)(8)14), or unrelated (37). However, the ambiguous relationship may result from the fact that business cycles may have asymmetric effects on population health.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A large strand of literature focused on the (mental/physical) health-income relationship in a growth context (see Ruhm (2000Ruhm ( , 2003Ruhm ( , 2005, van den Berg et al (2017), Swift (2011), Chen (2017), 5 From a methodological point of view, exactly this point makes our paper different from, inter alia, Svensson and Krüger (2012) or Chen (2017). 6 One explanation for this finding is that during 1956-1993, shocks such as the Vietnam and the second Gulf war have a stronger effect for men's than for women's life expectancy.…”
Section: Related Literaturementioning
confidence: 98%
“…5 / 29 Gerdtham and Johannesson (2005), Lam and Piérard (2017) or Svensson and Krüger (2012)). See Hollingsworth et al (2018) for a recent review of much of this research.…”
Section: Related Literaturementioning
confidence: 99%